Medical Cannabis for the Primary Care Physician. (October 2019) - Slawek, Deepika; Meenrajan, Senthil Raj; Alois, Marika Rose; Comstock Barker, Paige; Estores, Irene Mison; Cook, Robert
Medical cannabis use is common in the United States and increasingly more socially acceptable. As more patients seek out and acquire medical cannabis, primary care physicians will be faced with a growing number of patients seeking information on the indications, efficacy, and safety of medical cannabis. We present a case of a patient with several chronic health conditions who asks her primary care provider whether she should try medical cannabis. We provide a review of the pharmacology of medical cannabis, the state of evidence regarding the efficacy of medical cannabis, variations in the types of medical cannabis, and safety monitoring considerations for the primary care physician.